2018
DOI: 10.1186/s12903-018-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushing: to the best of one’s abilities is possibly not good enough

Abstract: BackgroundWeaknesses in toothbrushing performance can be seen when young adults are instructed to perform habitual toothbrushing. Nothing is known about toothbrushing behavior when instructed to perform to the best abilities. The present study analyzes such behavior and compares it to habitual behavior.MethodsA random sample of N = 98 young adults born in 1995 was examined in 2014/2015.They were asked to perform oral hygiene to the best of their abilities in front of a camera. Videos were analyzed regarding de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 16 publications
8
59
1
Order By: Relevance
“…The results of the present study thus support what has been found earlier [46, 8, 10]: Young adults appear to have problems to remove all plaque deposits even when they are brushing without any time limit and to the best of their abilities. The present study furthermore extends this result in showing that this problem is not confined to users of a manual toothbrush but exists to the same extent in daily users of a powered toothbrush.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of the present study thus support what has been found earlier [46, 8, 10]: Young adults appear to have problems to remove all plaque deposits even when they are brushing without any time limit and to the best of their abilities. The present study furthermore extends this result in showing that this problem is not confined to users of a manual toothbrush but exists to the same extent in daily users of a powered toothbrush.…”
Section: Discussionsupporting
confidence: 91%
“…Persons who habitually use a manual toothbrush appear to have difficulties to achieve oral cleanliness even when brushing to the best of their abilities [410]. Therefore, the present study aimed to assess whether daily users of a powered toothbrush would show results that are more favorable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of behavioral analysis are reported in related work (see Deinzer, Ebel, et al 2018). Briefly, the videos were analyzed with Mangold INTERACT 14 software.…”
Section: Observed Oral Hygiene Behaviormentioning
confidence: 99%